MYCOMIX - Exploring the toxic effects of mixtures of mycotoxins in infant food and potential health impact: final report - Alvito, Paula (2016)
Within this final report a detailed description of all tasks of the MYCOMIX project including a global evaluation is enclosed. The present project aims to explore the toxic effects of mixture of mycotoxins in infant food and potential health impact and includes a 1st task on multimycotoxin determination and legislation values, a 2nd on the evaluation of toxic effects of mycotoxin mixtures, a 3rd on bioaccessibility and absorption studies, a 4th on children exposure assessment and a final evaluation, the 5th task, on children´s health and mycotoxin mixtures. All tasks include an initial background and aims, materials and methods, results, deviations/comments, conclusions, references and project indicators. A final description of the total project output indicators is also included.